Enhanced Zeta Converter for DC Bus Voltage Regulation - P. Suresh; D. Kirubakaran (Institute of Advanced Engineering and Science, 2017)
In this paper, an Enhanced Zeta Converter (EZC) along with a high voltage gain converter is presented for DC Bus voltage regulation. The enhanced zeta converter consists of capacitors connected in parallel with the conventional zeta structure. The proposed zeta converter is applied to the Photo Voltaic system (PV) The well known Maximum Power Point Tracking (MPPT) P & O algorithm is used to extract maximum power from the photovoltaic system. The increased voltage is obtained with reduced number of switches using the proposed structure. The results to the proposed structure are compared with the conventional topology. The proposed converter is simulated using MATLAB and the same is verified with the hardware.